Characterization of the 1966 Camp Century subglacial core: a multiscale analysis - C. M. Collins; N. Perdrial; N. Perdrial; P.-H. Blard; P.-H. Blard; N. Keulen; W. C. Mahaney; H. Mastro; J. Souza; D. M. Rizzo; Y. Marrocchi; P. C. Knutz; et al. (Climate of the Past)
In 1966, drilling at Camp Century, Greenland, recovered 3.44 m of subglacial material from beneath 1350 m of ice. Although prior analysis of this material showed that the core includes glacial sediment, ice, and sediment deposited during an interglacial period, the subglacial material had never been thoroughly studied. To better characterize this material, we analyzed 26 of the 30 core samples remaining in the archive. We performed a multiscale analysis including X-ray diffraction (XRD), micro-computed tomography (μCT), and scanning electron microscopy (SEM) to delineate stratigraphic units and assign facies based on inferred depositional processes.